AN OVERVIEW OF CORPORATE GOVERNANCE PRACTICES OF SELECTED ISLAMIC BANKS: CASE OF RHB ISLAMIC BANK, MASRAF AL RAYAN AND EUROPEAN ISLAMIC INVESTMENT BANK - Zainab Belal; Tn. Hj. Mustapha Hamat (Jurnal Ekonomi dan Bisnis, 2016)
Complying with CG standards is not mandatory but with collapse of many financial institutions,compliance with high standards of CG in banking operation became a necessity. This is dueto the fact that many banks and companies worldwide collapsed as a result of poor corporategovernance practices such as Bank of Credit and Commerce International (BCCI) 1991,Enron 2001, WorldCom 2001, etc. Therefore, the objective of this paper is to examine andascertain whether present level of CG standards practiced by Islamic banks is adequate toprevent the banks from collapsing. The approach of the study is to evaluate the effectiveness ofBoard and the various Board Committees utilizing data published in financial statement of theselected banks. The study finds out that the selected banks comply with CG standards adopted,however such compliance does not mean that the board, committees will be constantly reliable.Therefore, instilling the Islamic values such as the concepts of Ehsan, honesty, accountability isparamount to prevent CG failures and protect banks from collapsing.Keywords: corporate governance, Islamic banks, board, committees.